Effect of graphene oxide loading on cobalt oxide performance as electrocatalyst for methanol oxidation reaction - Javed, Omama; Radhiyah, Abd Aziz (2022)
In this paper, cobalt oxide with graphene oxide included were prepared using a straightforward hydrothermal approach in this study for the electrocatalytic oxidation of methanol. Scanning electron microscopy (SEM), and X-ray diffraction (XRD), FTIR, and XPS techniques were used to evaluate the produced cobalt oxide with graphene oxide. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) techniques were used to examine the electrochemical behaviour of an electrode modified with GO-CO3O4. In regard to the oxidation of methanol in an alkaline medium, the electrocatalytic performances of electrodes modified with graphene oxide at various graphene oxide weight percentages were examined. The grapheme oxide, and cobalt oxide modified electrodes, the GO-CO3O4 modified electrode displayed higher current density brought on by the oxidation of methanol.